Ocorrência e diversidade de ácaros (Acari, Arachnida) associados a Tabebuia roseo-alba (Ridl.) Sand (Bignoniaceae), no município de São José do Rio Preto, São Paulo, Brasil - Feres, Reinaldo José Fazzio [UNESP]; Bellini, Marcos Roberto [UNESP]; Rossa-Feres, Denise de Cerqueira [UNESP] (Sociedade Brasileira de Zoologia, 2003)
This study reports the mite fauna associated with Tabebuia roseo-alba, a native and ornamental tree, determining the abundance and seasonal occurrence of species and the diversity of the community. Twenty three species were found belonging to 11 families, 10 of predatory habits and five phytophagous. The food habits of the eight remaining species are not known. Besides the great richness, the diversity was small, as consequence of the dominance of Lorryia formosa Cooreman, 1958 and Aculus sp., the most abundant species. These species occurred in the same microhabitat but with seasonal segregation: L. formosa was the most abundant in the dry season, while Aculus sp. occurred only in the rainy season. In August, when the plant lost its leaves, the following species were found in the apical branch structures: Brevipalpus sp. (aff. phoenicis), Cheletogenes sp., Euseius citrifolius Denmark & Muma, 1970, Lorryia formosa, Pronematus sp., and diapause females of Tenuipalponychus tabebuiae Aguilar, Flechtmann & Ochoa, 1991. In September, with leaves growing again, Aceria sp. was the only species on the plant, and its abundance decreased accentuately in October. The richness and the abundance of the mite fauna were not correlated with the temperature or the precipitation. These data suggest that the plant phenology was more important than the climate in the occurrence of species.
Occurrence and diversity of mites (Acari, Arachnida) associated with Tabebuia roseo-alba (Ridl.) Sand (Bignoniaceae), from São José do Rio Preto, São Paulo State, Brazil
Keywords: Acari; Bignoniaceae; Biodiversity; ecology; Mites; Tabebuia roseo-alba